Rates of neglect in a national sample: Child and family characteristics and psychological impact. (February 2019) - Vanderminden, Jennifer; Hamby, Sherry; David-Ferdon, Corinne; Kacha-Ochana, Akadia; Merrick, Melissa; Simon, Thomas R.; Finkelhor, David; Turner, Heather
Abstract: Background: Childhood neglect is an understudied form of childhood maltreatment despite being the most commonly reported to authorities. Objective: This study provides national estimates of neglect subtypes, demographic variations in exposure to neglect subtypes, and examines the psychological impact. Participants and Setting: Pooled data from two representative U.S. samples from the National Surveys of Children's Exposure to Violence (NatSCEV) survey conducted in 2011 and 2014, representing the experiences of children and youth aged 1 month to 17 years (N = 8503). Methods: Telephone surveys were used to obtain sociodemographic characteristics, six measures of past year and lifetime exposure to neglect, and assessments of trauma symptoms, suicidal ideation, alcohol use, and illicit drug use. Results: More than 1 in 17 U.S. children (6.07%) experienced some form of neglect in the past year, and more than 1 in 7 (15.14%) experienced neglect at some point in their lives. Supervisory neglect, due to parental incapacitation or parental absence, was most common. Families with two biological parents had lower rates (4.29% in the past year) than other household configurations (range from 7.95% to 14.10%; p < .05 ). All types of neglect were associated with increased trauma symptoms and suicidal ideation (for 10–17 year olds), and several were associated with increased risk of underage alcohol and illicit drug use. Conclusion: More attention needs to be paid to the impact of supervisory neglect. These results underscore the importance of prevention strategies that provide the supports necessary to build safe, stable, and nurturing relationships and environments that help children thrive.